Gene by Diet Interactions on Epigenetic Changes Modulating Cardiovascular Disease Risk Factors. - Ma, Yiyi. (2017)
Abstract: Background: Evidence has been steadily accumulating to document gene-by-environment (G×E) interactions for cardiovascular disease (CVD) related traits. However, the underlying mechanisms are still unclear. DNA methylation, one of the epigenetic mechanisms directly affecting genetic nucleotides and their interaction with regulatory proteins, may represent one of the potential mechanisms for the observed G×E interactions, based on its role as the interface between the `nature' and `nurture'. Objectives: To explore the interplay among DNA methylation, genetic variants, and environmental factors, we examined 1) the association between single nucleotide polymorphism (SNP) and DNA methylation; and 2) the role that DNA methylation plays in G×E interactions. Methodology: We applied a genome-wide approach with an integrated bioinformatics analysis to publicly available datasets of both genotypes (the HapMap project) and methylation patterns in B lymphocyte cell line (the Encyclopedia of DNA Elements (ENCODE) project) to explore the relationship between SNPs and DNA methylation patterns. A candidate gene approach was utilized to explore the potential mechanistic role that DNA methylation plays in significant G×E interactions at CVD-related loci, including APOE, IL6, ABCA1, APOA5, PCSK9, HMGCR and HNF1A. DNA methylation was measured by the Infinium Human Methylation 450K BeadChip in the Genetics of Lipid Lowering Drugs and Diet Network (GOLDN) study. Meta-analysis with 7 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium was conducted to explore the G×E interactions for blood lipids. Correlation between DNA methylation and gene expressions across 17 available cell lines in the ENCODE consortium were analyzed. Results: On a genome-wide scale, DNA methylation patterns are associated with haplotypes of multiple CpG-related SNPs (CGSs) within the same linkage disequilibrium (LD) block (P < 0.0001). At the APOE locus, the promoter SNP rs405509 interacts with age in the GOLDN population to modulate the methylation of the promoter CpG site cg01032398 (P = 0.03). At the IL6 locus, erythrocyte N3 polyunsaturated fatty acids (PUFAs) interact with the promoter SNP rs2961298 to modulate the methylation of a promoter CpG site cg01770232 (P = 0.02), which was suggested as a potentially functional methylation site based on its consistent correlation with IL6 gene expression in ENCODE (P = 0.0005) and plasma concentration of IL6 in GOLDN (P = 0.03). Meta-analysis with 7 cohorts in the CHARGE consortium found nominal interactions between circulating eicosapentaenoic acid (EPA) and the ABCA1 promoter SNP rs2246293 for blood high-density lipoprotein (HDL) cholesterol level (P = 0.006), and between circulating alpha-linolenic acid (ALA) and APOE promoter SNP rs405509 for plasma triglyceride (TG) (P = 0.01). Analysis with methylation in GOLDN and gene expression in ENCODE suggested that the genotype-dependent methylation of CpG site cg14019050 (P = 3.51×10-18 and 0.007 for association and interaction analysis, respectively) and cg04406254 (P = 0.008 and 0.009 for association and interaction analysis, respectively) may be mechanistically linked to the observed interactions of loci of ABCA1 and APOE, respectively. Conclusion: DNA methylation patterns are associated with haplotypes of multiple CGSs within the same LD block. Genotype-dependent methylation may account, in part, for the mechanisms underlying observed G×E interactions in APOE, IL6, and ABCA1. Our studies call for further demonstration with interventional studies and molecular mechanistic experiments, with the ultimate goal of providing fundamental evidence to support genetically-based strategies for the development of personalized medical care.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Jose Ordovas.; Committee: Caren Smith, Paul Jacques, Jean-Marc Zingg, and Sang-Woon Choi.; Keywords: Nutrition, Genetics, and Epidemiology.